Psychodynamics of transference and countertransference in the psychotherapy with sexual trauma - Mariia Tyshchenko (The Global Psychotherapist)
In this article, we emphasize the nature of transference and countertransference while working with sexual trauma. Such kind of trauma can evoke intense emotional, cognitive, and somatic reactions. In order to avoid projective distortions and maintain the therapeutic stance, therapists need to develop an awareness of their reactions and use this dynamic as a pathway to a deeper understanding of the client's or patient’s trauma. This article reviews theoretical perspectives from classical psychoanalysis to positive psychotherapy, illustrating methods for identifying and using transference and countertransference as therapeutic tools. In addition, the article discusses the prevalence and impact of sexual abuse on mental health. It describes how these psychodynamic processes work within an evidence-based framework to support emotional recovery. This article emphasizes the need for ongoing self-reflection and supervision for therapists to prevent professional burnout and increase their therapeutic effectiveness while working with patients and clients with sexual trauma.